Inexpensive Handheld Device for the Construction of High-Density Nucleic Acid Arrays. (December 1997) - Schummer, M.; Ng, W.-l.; Nelson, P.S.; Bumgarner, R.E.; Hood, L.
We report an easy-to-use, 384-pin handheld arraying and replicating device (ARD) for constructing high-density replicas of nucleic acids and E. coli transformants. We have modified an existing 384-pin tool to include a novel guide system to ensure vertical pin movement and enhance reproducibility. An asymmetric rectangular multiplexing frame is designed to increase the array density to 1536 dots on a standard microplate-size nylon membrane and to reduce the time and effort involved in producing array replicas. Our initial studies used the ARD to construct 1536-dot arrays of ovarian cDNA clones. We have hybridized these arrays with 32 P-labeled probes, which resulted in distinctive signals for either visual interpretation or semiautomatic spot detection and signal integration.